Influence of Environmental Conditions and Genetic Background of Arabica Coffee (C. arabica L) on Leaf Rust (Hemileia vastatrix) Pathogenesis - Toniutti, Lucile; Breitler, Jean-Christophe; Etienne, Hervé; Campa, Claudine; Doulbeau, Sylvie; Urban, Laurent; Lambot, Charles; Pinilla, Juan-Carlos H.; Bertrand, Benoît (Frontiers in Plant Science, 2017)
Global warming is a major threat to agriculture worldwide. Between 2008 and 2013, some coffee producing countries in South and Central America suffered from severe epidemics of coffee leaf rust (CLR), resulting in high economic losses with social implications for coffee growers. The climatic events not only favored the development of the pathogen but also affected the physiological status of the coffee plant. The main objectives of the study were to evaluate how the physiological status of the coffee plant modified by different environmental conditions impact on the pathogenesis of CLR and to identify indicators of the physiological status able to predict rust incidence. Three rust susceptible genotypes (one inbred line and two hybrids) were grown in controlled conditions with a combination of thermal regime (TR), nitrogen and light intensity close to the field situation before being inoculated with the rust fungus Hemileia vastatrix. It has been demonstrated that a TR of 27-22°C resulted in 2000 times higher sporulation than with a TR of 23–18°C. It has been also shown that high light intensity combined with low nitrogen fertilization modified the CLR pathogenesis resulting in huge sporulation. CLR sporulation was significantly lower in the F1 hybrids than in the inbred line. The hybrid vigor may have reduced disease incidence. Among the many parameters studied, parameters related to photosystem II and photosynthetic electron transport chain components appeared as indicators of the physiological status of the coffee plant able to predict rust sporulation intensity. Taken together, these results show that CLR sporulation not only depends on the TR but also on the physiological status of the coffee plant, which itself depends on agronomic conditions. Our work suggests that vigorous varieties combined with a shaded system and appropriate nitrogen fertilization should be part of an agro-ecological approach to disease control.